Carotid bypass surgery for a persistent neck tumor after multiple treatments: a case report (Medical Journal of Indonesia, 2022)
Carotid artery involvement in head and neck cancer is challenging for surgeons and oncologists, particularly in recurrence or residual disease following multiple treatments. However, carotid artery resection and reconstruction can be safely performed in a carefully selected patient with local and regional control benefits despite the potential morbidity and high-risk complications. We presented a case of primary laryngeal cancer treated with chemoradiotherapy, modified radical neck dissection type I for residual neck node disease, and further chemotherapy. Although the primary laryngeal cancer showed a complete response, the residual neck tumor was still unresolved and even involved the carotid artery. Therefore, carotid resection with a combined saphenous vein graft and free flap reconstruction was the treatment of choice for this patient. It is effective and safe, and the risk of morbidity has been accepted.